Prevention of Child Sexual Abuse: Parents' Knowledge, Attitudes and Practices - S Khanjari; F Bastani; R Kamalinahad; AF Hosseini (Iran University of Medical Sciences, 2014)
Abstract Background & Aims: Sexual abuse is the most damaging type of abuse which has been increased significantly in recent decades so prevention of sexual abuse is crucial. This study aimed to determine the knowledge, attitude and practices of parents regarding child sexual abuse prevention program in elementary school and preschool children. Material & Methods: In this descriptive study, 536 parents of elementary and preschool children in schools of Arak, were enrolled by cluster random sampling. Data was collected by child sexual abuse (CSA) questionnaire and analyzed descriptive statistics using SPSPC (v. 16).  Results: The results showed that of all parents, 343 (66%) had good knowledge and 177 (34%) had poor knowledge about the prevention of sexual abuse of children. Of all parents, 383 (80.63%) had good attitude and 92 (19.37%) had poor attitude toward prevention education of sexual abuse. Also 456 parents (85.71%) had good performance and 76 parents (14.29%) had poor performance regarding prevention of sexual abuse. Conclusion: Considering the poor knowledge a one third of the parents regarding the prevention of sexual abuse, providing strategies to increase their knowledge seem necessary.